2023
DOI: 10.1038/s41420-023-01398-x
|View full text |Cite
|
Sign up to set email alerts
|

Serine and one-carbon metabolism sustain non-melanoma skin cancer progression

Abstract: Non-melanoma skin cancer (NMSC) is a tumor that arises from human keratinocytes, showing abnormal control of cell proliferation and aberrant stratification. Cutaneous basal cell carcinoma (cBCC) and cutaneous squamous cell carcinoma (cSCC) are the most common sub-types of NMSC. From a molecular point of view, we are still far from fully understanding the molecular mechanisms behind the onset and progression of NMSC and to unravel targetable vulnerabilities to leverage for their treatment, which is still essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Serine metabolism might play a key role in maintaining metabolic homeostasis and health 18 . And serving as a primary source of one-carbon units, serine is a significant contributor to cancer metabolism 19 (non-melanoma skin cancer 20 , pancreatic cancer 21 , and lung cancer 22 ). It has been reported that drugs, targeting serine-related one-carbon metabolic pathway, could inhibit the proliferation of cancer cells 23 , such as bladder cancer 24 , and endometrial cancer 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Serine metabolism might play a key role in maintaining metabolic homeostasis and health 18 . And serving as a primary source of one-carbon units, serine is a significant contributor to cancer metabolism 19 (non-melanoma skin cancer 20 , pancreatic cancer 21 , and lung cancer 22 ). It has been reported that drugs, targeting serine-related one-carbon metabolic pathway, could inhibit the proliferation of cancer cells 23 , such as bladder cancer 24 , and endometrial cancer 25 .…”
Section: Discussionmentioning
confidence: 99%